PENGARUH CAMPURAN MEDIUM TANAM DAN VOLUME PEMBERIAN AIRTERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DIPEMBIBITAN UTAMA - Anton Tantowi Yahya; Islan Islan; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the effect of growing media combination and water application volume and to determine the best treatment on the growth of palm oil seedling (Elaeis guineensis jacq.)in main nursery. The research was carried out at the Agriculture experimental station faculty of agriculture, University of Riau, from September 2015 to Desember 2015. The research used Completely Randomized Design (CRD) with two factors. Fist factor is growing medium combination consist of 3 levels of mixture ratio, M1 : Red Yellow Podzolic and Peat(1 : 1), M2 : Red Yellow Podzolic and Peat(2 : 1),M3 : Red Yellow Podzolic and Peat(3 : 1), second factor is water application volume consist of 3 levels which are, V1 : 800 ml/day, V2 : 1.000 ml/day, V3 : 1.200 ml/day. Data were analyzed with further test Duncan’s New Multiple Range Test (DNMRT) at 5%. Parameter observed are seedling height, number of leaf, stem diameter and leaf area. The result of the research showed that the usage of growing medium combination such Red Yellow with Peat Soil 2 : 1 and water application volume 1,2 l/day tend to give good palm oil seedling growth. It is suggested to carry further research with the addition more fertilizer sothat will influence all parameter.Key word ; peat, red yellow podzolic, palm oil seedling, water application volume.